Error Bounds for Corrected Euler-Maclaurin Formula in Tempered Fractional Integrals (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, an equality is established for tempered fractionalintegrals. With the help of this equality, we prove several corrected Euler-Maclaurin-type inequalities for the case of differentiable convex functions involving tempered fractional integrals. Moreover, we provide our results byusing special cases of obtained theorems.